Proteína hidrolisada de frango para tilápia do Nilo: digestibilidade e desempenho produtivo - Rocha, Joana D'Arc Mauricio (2018)
The growing demand for quality protein ingredients for animal nutrition requires the prospection of alternative foods that meet the nutritional needs of farm animals. In this sense, the present study aimed to determine the apparent digestibility coefficient of the nutrients of the hydrolyzed chicken protein (PHF) and to evaluate the productive performance of Nile tilapia post-larvae and fingerlings fed diets containing increasing levels of this product. In order to determine the digestibility, 240 juveniles of tilapia distributed in DIC with two treatments (reference ration and test ration) and four replicates were used in a system composed of eight tapered cylinder tanks adapted for fecal collection. Two diets were made, one reference and the other composed of 80% of the reference diet and 20% of the hydrolyzed chicken protein, both with 0.1% chromium oxide. The animals were adapted to the conditions and experimental diets for seven days, and in the following 14 days the daily food handling, cleaning of the structures and the faeces were collected for 12 consecutive hours (night time). The material (PHF, rations and faeces) was analyzed for its chemical composition, chromium quantification and amino acid profile, for further calculation of the digestibility coefficients. In the evaluation of the productive performance of Nile post-larvae, a DIC with five treatments was used, which consisted of diets with PHF inclusion levels (0, 2.5, 5, 7.5 and 10%) and three replicates, 15 experimental units. 72 animals were allocated in each tank with 70 liters of useful volume. In the performance test of Nile tilapia fingerlings, 420 animals were distributed in ICDs in seven treatments and four replicates, making 28 tanks with 70L capacity. Six diets containing increasing levels of PHF (1, 2, 3, 4, and 6%) were elaborated, besides a control treatment (absence of PHF). In both performance tests, the animals were fed for 30 days and at the end of the experimental period the weight and total length measurements were taken to calculate the productive parameters. The data were submitted to analysis of variance and when significant to the Tukey test (p <0.05) or polynomial regression. The apparent digestibility coefficient (CDA) of the protein and energy of PHF was 93.61 and 93.86%, respectively. The CDA of the amino acids varied from 94.02 to 97.55%, presenting values of 97.55; 96.84 and 94.13% for lysine, methionine and threonine, respectively. The PHF positively influenced the final weight, final length, weight gain and specific growth rate of Nile tilapia post-larvae, with better results for the inclusion of 2.5% of this product in the diets (p <0.05) . In the fry trial, the final weight, weight gain, specific growth rate, trimming feed rate and protein efficiency ratio were influenced by the inclusion of PHF, with optimum inclusion varying from 2.91 to 3.62%. However, Nile tilapia efficiently utilized PHF demonstrated by high nutrient and energy CDA levels, as well as providing improvements in the productive aspects of Nile tilapia post-larvae and fingerlings. Therefore, it is recommended to include 2.5% of PHF in the diet for post larvae and 3% for fingerlings of the same species.